Inflammatory bowel disease in married couples: 10 cases in Nord Pas de Calais region of France and Liège county of Belgium. Issue 9 (September 1994) - Comes, M C; Gower-Rousseau, C; Colombel, J F; Belaïche, J; Van Kruiningen, H J; Nuttens, M C; Cortot, A
Abstract : Ten pairs of husband-wife couples are reported with inflammatory bowel disease who were seen in the same geographical area in Nord Pas de Calais region of France and in Liège county (Belgium). Among these 10 couples, four were concordant for Crohn's disease, two for ulcerative colitis, and four were discordant. In nine of 10 couples neither spouse had symptoms before marriage but inflammatory bowel disease subsequently developed in both. In one couple, one spouse had Crohn's disease before marriage and the other partner experienced symptoms afterwards. Eighteen children were born to eight of 10 couples. Five of them developed Crohn's disease but four belong to the same family. In all cases the affected children were born to parents who both developed Crohn's disease after they had married and were conceived at a time when parents did not yet have symptoms. It is proposed that this pattern of emergence of inflammatory bowel disease suggests a role for an infectious agent yet to be identified.